Pilotage: sea the change - January, Marlene Gillian (Centre for Law and Society, 2026)
The Shipping Industry has recently undergone a change in legislation, which is not unusual for such a constantly evolving industry. The National Ports Act 12 of 2005 ("the Act") was approved by the National Assembly on I March 2006 and it came into operation on 26 November 2006. Most of the provisions in Chapter 9 of the Act have been kept the same as the previous legislation' however section 76 of the Act effects a significant change from the previous manner in which liability for pilot error has been treated. Under the previous dispensation both the pilot and the port authority were exempt from liability for loss or damage caused by the pilot's negligence. The onus rested with the Port Authority who had to prove that the negligence were only due to error in order to rely on the exemption of liability clause. The National Port Authority has now repealed those provisions of the previous legislation and replaced it with section 76 of the Act. Under the provisions of s 76 the exemption is for the consequences of the pilot's acts or omissions in good faith'. Under the previous dispensation, courts have interpreted the meaning of the word 'negligent' and in the last leading case2 relating to such interpretation, it left the question hanging without any final conclusion, except for the fact that the word 'negligent' should be interpreted in the narrow sense. Under the provisions of section 76 the word • negligence' has been removed and replaced with the words' good faith'.